Leak detection in liquid transmission pipelines using simplified pressure analysis techniques employing a minimum of standard and non-standard measuring devices. (15th April 2016) - Ostapkowicz, Paweł
Highlights: An experimental pipeline allows us to carry out a comprehensive program of research. We examine a minimum and non-minimum hardware variants of leak detection methods. We test a non-standard technique for measuring additional non-standard signals. The additional non-standard signals are showed to have useful metrological properties. Effective algorithms aimed at detection and location of leaks are presented. Abstract: This paper deals with issues of detecting leaks in liquid transmission pipelines. It presents solutions of procedures (algorithms) applied to both negative pressure wave and gradient methods. These algorithms are aimed at achieving a satisfactory level of efficiency of a single leakage diagnosis. The methods are evaluated in terms of their implementation with a minimum number of measuring devices. In the case of the negative pressure wave method, apart from the standard pressure transmitters to measure the pipeline pressure, also the use of non-standard measuring devices, conventionally the so-called correctors, is considered. The signals generated by the correctors are characterized by good correspondence of the measured signal representing a change in the pressure to measurement noise level and the overall pressure transmitter range. All this, in combination with the developed algorithm, which apart from detecting a leak, is aimed at precise identification of a change in the signal related to the wave pressure front, i.e. the so-called inflection point, provides a high efficiency of leak detection. This has been proven by carrying out a number of experimental tests on a laboratory water pipeline. The tests involved simulations of both sudden as well slow leakages.